Direct cost of wound dressing in Nigeria: Implications for catastrophic healthcare expenditure - K.D. Ogundeji; P.R. Risenga; G.B. Thupayagale-Tshweneagae (Elsevier, 2023)
Background: Studies on wound care continue to report high cost of care for various types of wounds. However, little attention is given to specific costs incurred on wound dressing among hospitalized patients. This study highlighted the estimated cost required for successful wound dressing in Nigeria, with its catastrophic implications for healthcare expenditure. Method: A descriptive cross-sectional research design was adopted. Every patient who had spent no less than four weeks in the ward or had already been discharged was interviewed. Variables of interest included number and cost of dressing packs used per week. The data was analyzed by Statistical Package for Social Sciences (SPSS) version 23 and presented in frequency tables, percentages, mean and standard deviations. Note: US$1 = ₦575 in October 2021. Result: Findings show that the mean age of the respondents was 44.95 ± 16.12. Two-thirds were male artisans and traders with no less than a high school level of education. Over 70% of the respondents have a family size of between 5 and 10 members and over 50% earn less than ₦50000 per month. 50% received a daily dressing, requiring 1-5 moderate or major dressing packs per week. On a weekly basis, the average cost of wound dressing was between ₦9000-₦27000 while per acute care episode was between ₦50000-₦120000. Conclusion: The cost of wound dressing and hospitalization is high for the average Nigerian citizen/family. The Nigerian government should extend its low-income-friendly health insurance programme to reduce the incidence of catastrophic healthcare expenditure emanating from continual wound dressing.